A comparative analysis of banking institutions: examining quiet life. Issue 6 (10th June 2019) - Doyran, Mine Aysen; Santamaria, Zachary Roman
Abstract : Purpose: The purpose of this paper is to analyze the performance of banking institutions in Costa Rica over the period 2004–2014. Design/methodology/approach: This paper employs system GMM, dynamic panel data and traditional financial hypothesis framework to analyze bank performance and assess marketplace sustainability for a sample of commercial and cooperative banks from Costa Rica. In the assessment, the authors visit the relative market power, structure conduct performance (SCP) and efficient structure literature. Findings: Market share (MS) is positively related to performance whereas the authors find a negative effect of market concentration (Herfindahl–Hirschman index) on bank profits, thereby refuting the SCP hypothesis. The authors accept the "quiet life" hypothesis within Costa Rican banks since a moderate level of profit persistence is detected. Commercial banks are less profitable. Yet when crisis is introduced to the models, it has a significant and negative impact on overall bank performance. Research limitations/implications: The authors selected years and banks based on available data plus default information in the relevant database. More insights can be gained from post-2014 developments. Practical implications: The current results and conclusions have implications for developing economies (and economic development, in general) by showing that the traditional understanding of cooperative bank model as better for the public good may not be necessarily true. They offer insight into the understanding of how different bank-type institutions affect the public good. Furthermore, expanding the research to Latin America in order to directly compare commercial and cooperative enterprises via a meta-frontier technique would help buttress this evidence. Originality/value: This is the most recent study to provide such an investigation for a Latin American country with a sizable MS for cooperative and public sector banks. The paper offers analysis that has been limited in Latin American banking markets thus far.